2007
DOI: 10.1007/s00360-007-0204-1
|View full text |Cite
|
Sign up to set email alerts
|

Localization of aquaporin-2, renal morphology and urine composition in the bottlenose dolphin and the Baird’s beaked whale

Abstract: This study examined the distribution pattern of aquaporin-2 (AQP2), relative medullary thickness (RMT) and urine properties in the bottlenose dolphin Tursiops truncatus and Baird's beaked whale Berardius bairdii. Immunohistochemical studies revealed that AQP2 was localized in the collecting tubules/ducts of both species' renicules, as in terrestrial mammals. The collecting ducts with AQP2 were thinner and arranged more densely in the dolphin than in the whale. RMT values in the renicule were moderate in both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…9). 26,32,38,39 Glutathione S-transferase-a GST-a had variable expression within the dog kidney. Interestingly, the transitional epithelium lining the renal papilla of some dogs was positive for GST-a staining along the cell borders and diffusely throughout the nucleus (Fig.…”
Section: Aquaporinmentioning
confidence: 99%
“…9). 26,32,38,39 Glutathione S-transferase-a GST-a had variable expression within the dog kidney. Interestingly, the transitional epithelium lining the renal papilla of some dogs was positive for GST-a staining along the cell borders and diffusely throughout the nucleus (Fig.…”
Section: Aquaporinmentioning
confidence: 99%
“…The concentrations of corresponding constituents in the urine of fin whales and bottlenose dolphins were obtained from literature (Kjeld 2001;Suzuki et al 2008) and compared with those of the freshwater and marine finless porpoise.…”
Section: Blood and Urine Analysismentioning
confidence: 99%
“…It was previously reported that AQP2 is distributed in the principal cells of the kidneys of the bottlenose dolphin and Baird's beaked whale, similar to terrestrial mammals (Suzuki et al, 2008). During the process of the present study, unique data were unexpectedly obtained from rapid amplification of cDNA ends (RACE)-PCR experiments, indicating alternative splicing of the AQP2 gene expressed in many organs of bottlenose dolphin.…”
Section: Introductionmentioning
confidence: 70%
“…Immunohistochemical localization of AQP2 and alternative AQP2 in the kidney of the dolphin was determined using the method previously described (Suzuki et al, 2008). Alternative AQP2 distribution was also detected in another 15 organs (epidermis, esophagus, forestomach, main stomach, pyloric stomach, small intestine, liver, pancreas, spleen, adrenal gland, ovary, lung, muscle, heart and brain).…”
Section: Immunohistochemistry and Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation